2019
DOI: 10.1186/s12903-019-0760-2
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life: a retrospective study on local vs. microvascular reconstruction in patients with oral cancer

Abstract: Background New medicinal and surgical oncological treatment strategies not only improve overall survival rates but continually increase the importance of Health-Related Quality of Life (HRQOL). The purpose of this retrospective cross-sectional study was to analyze HRQOL of patients with oral squamous cell carcinoma after ablative surgery and to evaluate predictive factors for HRQOL outcome. Methods The study included 88 patients with histologically confirmed oral squamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…What is undisputed, however, is an increased morbidity and mortality associated with larger tumors, which require a comprehensive treatment regimen that includes both more extensive surgical and adjuvant procedures. Although the prognosis for patients with oral cancer has improved in recent decades, 16 the COVID‐19‐related increases in tumor size have a significant impact on prognosis 17 and quality of life 18,19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is undisputed, however, is an increased morbidity and mortality associated with larger tumors, which require a comprehensive treatment regimen that includes both more extensive surgical and adjuvant procedures. Although the prognosis for patients with oral cancer has improved in recent decades, 16 the COVID‐19‐related increases in tumor size have a significant impact on prognosis 17 and quality of life 18,19 …”
Section: Discussionmentioning
confidence: 99%
“…Although the prognosis for patients with oral cancer has improved in recent decades, 16 the COVID‐19‐related increases in tumor size have a significant impact on prognosis 17 and quality of life. 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…Fujimoto et al 30 reported similar findings regarding age; however, their study had a follow-up period of six months. Meier et al 31 reported similar findings regarding the tumor site, while Hahn et al reported similar findings regarding denture use. We identified illness duration (p = 0.005), drinking habit (p = 0.023), and diet (p = 0.035) as factors predicting the patients' quality of life at three months after the surgery.…”
Section: Discussionmentioning
confidence: 68%
“…Maxillectomy can result in severe functional problems resulting from impaired mastication and deglutition [14]. Maxillary defects following flap reconstruction are repaired using obturator prostheses, dentures, or implants [1214].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of massive malignant tumors of the maxilla can open communication between the oral, nasal, and orbital cavities, thereby resulting in hypernasal speech, food, and liquid countercurrent in the nasal cavity, dysphagia, masticatory disturbance, and facial disfigurement [14]. Free flap reconstruction can be used to repair various tissue defects resulting from removal of a maxillary carcinoma [5].…”
Section: Introductionmentioning
confidence: 99%